IMPLEMENTASI AKTIVITAS KETERAMPILAN HIDUP PRAKTIS DALAM MENINGKATKAN KEMANDIRIAN ANAK KELOMPOK A DI KECAMATAN KALIWEDI, KABUPATEN CIREBON - Mawad Datun Nisa; Cucu Sopiah; Rina Hizriyani (Bunayya, 2026)
The limited independence of early childhood learners in Group A at TK Permata Ujungsemi served as the primary rationale for this study. Independence is regarded as a fundamental developmental domain that needs to be fostered from an early stage, as it is closely related to a child’s ability to perform daily activities without relying on others. An improvement in children’s independence was pursued through practical life skills activities, using a Classroom Action Research approach over 2 cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The participants were 24 children aged 4–5 years. Data were collected through observation and documentation using an independent observation sheet. In contrast, data analysis was conducted using quantitative descriptive techniques, expressed as percentages, to track progress in each cycle. The findings indicated a gradual increase in children’s independence, from 25% in the pre-cycle stage to 54.17% in cycle I, and then to 95.83% in cycle II. Therefore, it can be concluded that practical life skills activities are effective in enhancing early childhood independence while also helping children become more confident in carrying out their daily routines.